ENZYMATIC DEGUMMING USING XYLANASE AND PECTINASE TO IMPROVE BRIGHTNESS AND FINENESS QUALITY OF RAMIE FIBER (Boehmeria nivea L.) AS TEXTILE RAW MATERIAL - Abidin, Kharis Yohan; Nurhayati, Niknik; Nandyawati, Dewi; Sabbathini , Gabriela Christy (BRIN - Badan Riset dan Inovasi Nasional, 2023)
Ramie (Boehmeria nivea L.) fiber is an alternative to cotton fiber, and the degumming process is crucial for preparing it as a textile raw material. This study investigates the enzymatic degumming of ramie fiber using a combination of xylanase enzyme from Bacillus halodurans CM1 and commercial pectinase enzyme. The objective is to assess the impact of enzymatic degumming on the physical properties (weight loss, whiteness index, tenacity, elongation, and fineness) of ramie fiber. The degumming process was conducted in a shaker incubator at a temperature of 50 °C, pH 9, and 150 rpm. The degumming treatment involved 3% v/v xylanase, 1% v/v pectinase, 1% v/v surfactant, and 0.05% v/v NaClO2. The results show that the bleaching treatment (S6) resulted in higher fiber weight loss (9.52%), whiteness index (87.87%), tenacity (20.08 g/Tex), and fineness (1.05 denier) compared to the non-bleaching treatment.